High-spin versus broken symmetry--Effect of DFT spin density representation on the geometries of three diiron (III) model compounds - Binning, R.C. Jr; Bacelo, Daniel E (Journal of computational chemistry, 2008)
Unrestricted density functional theory calculations have been conducted on three diiron(III) synthetic model compounds containing antiferromagnetically coupled high-spin (HS) irons for which crystallographic structures and Raman spectral data are available. Three density functionals have been employed: BPW91, PWC, and BOP. The study compares the effects on optimized geometries and harmonic vibrational frequencies of spin-paired (SP) low-spin, HS, and broken symmetry antiferromagnetically coupled singlet representations of the spin density distribution. The geometries around the diiron centers in the HS and broken symmetry (BS) representations are found to be similar, both markedly different from those arising from the SP representation. Small differences between the HS and BS results are seen in bond lengths, angles, Raman frequencies, and spin densities associated with oxo and peroxo bridges between the irons.